Self-reported symptoms in Swedish hairdressers and association with exposure to volatile organic compounds (VOCs), including aldehydes - Niklas Ricklund; Ing-Liss Bryngelsson; Jessika Hagberg (BMC, 2023)
Abstract Background Working as a hairdresser involves combined exposure to multiple chemicals in hair treatment products that may induce symptoms in airways and skin. Methods In this cross-sectional study, perceived symptoms among Swedish hairdressers at 10 hair salons were surveyed through a questionnaire. Associations with personal exposure to volatile organic compounds (VOCs), including aldehydes, and their corresponding hazard index (HI), based on the estimated risk for non-cancer health effects, were examined. The prevalence of four out of 11 symptoms was compared to available reference datasets from two other studies of office workers and school staff. Results All 11 surveyed symptoms were reported among the hairdressers (n = 38). For the whole study group, the most prevalent symptoms were dripping nose (n = 7) and headache (n = 7), followed by eczema (n = 6), stuffed nose (n = 5), cough (n = 5) and discomfort with strong odors (n = 5). Significant relationships between exposure and symptoms were scarce. The exception was total VOC (TVOC) exposure adjusted to worked years in the profession; a difference was observed for any symptom between hairdressers in the group with 20 + years compared to 0-5 years in the profession (logistic regression, OR 0.03, 95% CI 0.001-0.70). Out of the four symptoms available for comparison, the prevalence of headache and cough was significantly higher in hairdressers than in controls (OR 5.18, 95% CI 1.86-13.43 and OR 4.68, 95% CI 1.17-16.07, respectively). Conclusions Adverse health effects related to occupation was common among the hairdressers, implying a need for exposure control measures in hair salons. Symptoms of headache and cough were more frequently reported by hairdressers than staff in offices and schools. A healthy worker effect among the hairdressers was indicated in the group with 20 + years compared to 0-5 years in the profession. Significant relationships between measured exposure and symptoms were scarce but gave information about advantages and disadvantages of the different exposure measures. The study design could be improved by increasing the size of the study population, using a better match of reference data and increasing the applicability and representability over time of the measured exposure.